The influence of seat configuration on maximal average crank power during pedaling: A simulation study - Rankin, J. W.; Neptune, R. R. (Journal of Applied Biomechanics, 2010)
Manipulating seat configuration (i.e., seat tube angle, seat height and pelvic orientation) alters the bicyclerider geometry, which influences lower extremity muscle kinematics and ultimately muscle force and power generation during pedaling. Previous studies have sought to identify the optimal configuration, but isolating the effects of specific variables on rider performance from the confounding effect of rider adaptation makes such studies challenging. Of particular interest is the influence of seat tube angle on rider performance, as seat tube angle varies across riding disciplines (e.g., road racers vs. triathletes). The goals of the current study were to use muscle-actuated forward dynamics simulations of pedaling to 1) identify the overall optimal seat configuration that produces maximum crank power and 2) systematically vary seat tube angle to assess how it influences maximum crank power. The simulations showed that a seat height of 0.76 m (or 102% greater than trochanter height), seat tube angle of 85.1 deg, and pelvic orientation of 20.5 deg placed the major powerproducing muscles on more favorable regions of the intrinsic force-length-velocity relationships to generate a maximum average crank power of 981 W. However, seat tube angle had little influence on crank power, with maximal values varying at most by 1% across a wide range of seat tube angles (65 to 110 deg). The similar power values across the wide range of seat tube angles were the result of nearly identical joint kinematics, which occurred using a similar optimal seat height and pelvic orientation while systematically shifting the pedal angle with increasing seat tube angles.